Predictors of knowledge transfer between expatriates and host country nationals : shared vision as mediator - Zulkifly, Nurul Afiqah; Ismail, Maimunah; Hamzah, Siti Raba’ah (European Journal of Management and Business Economics, 2019)
Purpose – The purpose of this paper is to investigate the influences of cultural intelligence, feedback-seeking behavior and shared vision as a mediator on bi-directional knowledge transfer involving expatriates and host country nationals (HCNs). Design/methodology/approach – This paper integrates the signaling theory, the social capital theory and the anxiety and uncertainty theory in investigating the relationships between predictors and knowledge transfer in a bi-directional manner. The participants of the study were 125 expatriate-HCN pairs of MNCs and local organizations in the areas of Klang Valley, Malaysia. Findings – Shared vision was found to significantly mediate the influences of cultural intelligence and feedback-seeking behavior on knowledge transfer as perceived by the respective respondents. Originality/value – Co-existence between expatriates and HCNs leads to many organizational outcomes including knowledge transfer. This paper additionally provides theoretical and practical implications to human resource practices.